Implementation of a cue-based aggregation with a swarm robotic system - Arvin, Farshad; C. Doraisamy, Shyamala; Samsudin, Khairulmizam; Ahmad, Faisul Arif; Ramli, Abdul Rahman (Springer, 2012)
This paper presents an aggregation behavior using a robot swarm. Swarm robotics takes inspiration from behaviors of social insects. BEECLUST is an aggregation control that is inspired from thermotactic behavior of young honeybees in producing clusters. In this study, aggregation method is implemented with a modification on original BEECLUST. Both aggregations are performed using real and simulated robots. We aim to demonstrate that, a simple change in control of individual robots results in significant changes in collective behavior of the swarm. In addition, the behavior of the swarm is modeled by a macroscopic modeling based on a probability control. The presented model in this study could depict the behavior of swarm throughout the performed scenarios with real and simulated robots.